A Fuzzy DEMATEL-ANP-Based Approach to Prioritize Activities in Enterprise Architecture. (15th March 2022) - Afshani, Jamshid; Karimi, Abbas; Osati Eraghi, Nafiseh; Zarafshan, Faraneh
Abstract : Prioritization of activities is a multicriteria problem that includes both quantitative and qualitative factors. Moreover, due to the nature of organizations and activities, the impact of activities on each other is fuzzy. Prioritizing activities in real and fuzzy situations will help an organization's decision makers to make the right decisions. In this paper, a new fuzzy hybrid methodology is proposed to describe and prioritize the activities of the organization in fuzzy conditions. First, the activities of the organization are described in a new fuzzy format based on activity model (OV-5) of the C4ISR framework. Furthermore, fuzzy DEMATEL is used to calculate the interdependencies between activities, and then fuzzy ANP is used to calculate the weight of each activity. Finally, by combining the results of the two methods, the priority of activities was calculated. Additionally, an empirical study is presented to illustrate the application of the proposed method.